2008
DOI: 10.1007/s11695-008-9657-x
|View full text |Cite
|
Sign up to set email alerts
|

Vagal Nerve Dissection During Pouch Formation in Laparoscopic Roux-Y-Gastric Bypass for Technical Simplification: Does it Matter?

Abstract: Pouch formation during RY-BP may be alleviated by simply dissecting the perigastric fatty tissue. In this way the anterior vagal trunk is dissected, however, no influence on clinical, functional and laboratory results occur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…At 12 or 18 months postsurgery, there was no difference in BMI and EWL between the two groups. Similar results were reported by Martin and Earle 168 for LAGB and by Perathoner and associates 143 for RYGB. In contrast, Kral and coworkers 169 had found that adding truncal vagotomy to VBG improved weight loss (51% versus 34% EWL).…”
Section: Vagus Nervesupporting
confidence: 89%
“…At 12 or 18 months postsurgery, there was no difference in BMI and EWL between the two groups. Similar results were reported by Martin and Earle 168 for LAGB and by Perathoner and associates 143 for RYGB. In contrast, Kral and coworkers 169 had found that adding truncal vagotomy to VBG improved weight loss (51% versus 34% EWL).…”
Section: Vagus Nervesupporting
confidence: 89%
“…[2][3][4] It is well established that both leptin and insulin decrease significantly after WL, 5,6 while ghrelin variations after WL show variable results. 5,[7][8][9][10][11][12][13][14][15][16] Although WL induced by caloric restriction is associated with an increase in plasma ghrelin, [8][9][10][11] ghrelin changes in WL post-bariatric surgery seem to be influenced by the type of surgical procedure in relation to gastric fundus resection 8,[12][13][14] or to the integrity of vagal fibers involved in ghrelin secretion, 7,15,17 with variable results reported after Roux-en-Y gastric bypass (RYGBP). 7,8,16,[18][19][20][21] These inconsistent results have been linked to differences in follow-up time or to the fact that patients were still actively losing weight when ghrelin was measured, as suggested by Faraj et al 17 At present, it is not well established whether the changes in ghrelin observed earliest when losing weight persist at long term.…”
mentioning
confidence: 99%
“…Additionally, vagal efferent signals have been shown to regulate the motility of the gastrointestinal tract directly through cholinergic signaling [86]. To date, the relevance of the vagal nerve for body weight after gastric bypass is incompletely understood [71,77,87]. We demonstrated previously that preserving vagal fibers of the dorsal vagal trunk during the gastric bypass operation may lead to greater and more sustained body weight loss in rats [17].…”
Section: Limb Lengthmentioning
confidence: 99%